2013
DOI: 10.1364/oe.21.016305
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and lasing investigations of Yb:YSGG crystal

Abstract: We report on a systematic study of the absorption and emission spectral properties of (Yb(0.1)Y(0.9))(3)(Sc(1.5)Ga(0.5))Ga(3)O(12) (Yb:YSGG) crystals. The broad fluorescence spectral lines indicate great potential of Yb:YSGG for tunable and ultrafast laser applications. Efficient continuous-wave (cw) laser oscillation was also demonstrated at room temperature (RT), generating an output power of 6.11 W with an optical-to-optical efficiency of 64.2%, and a slope efficiency of 80.1% with respect to absorbed pump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The study on its spectroscopic properties showing that the emission cross section amount to 1.05 Â 10 À20 cm 2 at the emission peak of 1024 nm. The fluorescence lifetime of 1.38 ms is longer than some other gallium garnets [2,7,[11][12][13] and it indicates the Yb:GAGG crystal has a great potential to get high energy pulse through Q-switching action [14]. As the reported, passively Q-switched operation has been demonstrated with many Yb-doped crystals [15,16], however, the active Q-switched laser action with acousto-optic (AO) modulator has not attracted much more attention.…”
Section: Introductionmentioning
confidence: 99%
“…The study on its spectroscopic properties showing that the emission cross section amount to 1.05 Â 10 À20 cm 2 at the emission peak of 1024 nm. The fluorescence lifetime of 1.38 ms is longer than some other gallium garnets [2,7,[11][12][13] and it indicates the Yb:GAGG crystal has a great potential to get high energy pulse through Q-switching action [14]. As the reported, passively Q-switched operation has been demonstrated with many Yb-doped crystals [15,16], however, the active Q-switched laser action with acousto-optic (AO) modulator has not attracted much more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Applying absorbing or reflecting optical color filters in front of individual photo-detectors is the most popular approach to WDM. [9,10] For example, Wu et al [10] reported a WDM system, which uses color selective dichroic filters to separate individual WDM links. This structure makes all color channels propagate along the same www.advopticalmat.de optical axis, maintaining collinearity, and compact design, but supports only point-to-point applications with limited FoV.…”
mentioning
confidence: 99%
“…Over the past few years, visible light communication (VLC) has received significant attention to moving parts of high-speed indoor data transmission. Unlike radio frequency (RF) wireless communication, VLC utilizes the already installed light emitting diode (LED) as data transmitters (Tx) [1][2][3][4][5] that can be applied in environments where RF is not necessarily allowed, such as airplanes and military facilities. Except, VLC has also been standardized for wireless personal area networks (WPANs) in Institute of Electrical and Electronics Engineers (IEEE) standard 802.15.7, and it aims to open the road for commercialization in both industry and academia [6] .…”
mentioning
confidence: 99%
“…(a)-(c) 49 constellations before STBC decoding of (1),(2), and (3); (a-1)-(c-1) 16 constellations after STBC decoding without channel optimization of (1),(2), and (3); (a-2)-(c-2) 16 constellations after STBC decoding with channel optimization of (1), (2), and (3).…”
mentioning
confidence: 99%